2016
DOI: 10.1088/1752-7155/10/4/046008
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of exhaled breath on Tenax TA

Abstract: Exhaled breath is coming to the forefront of non-invasive biomarker discovery efforts. Concentration of exhaled breath volatile organic compounds (VOCs) on thermal desorption (TD) tubes with subsequent analysis by gas chromatography-mass spectrometry (GC-MS) has dominated this field. As discovery experimentation increases in frequency, the need to evaluate the long-term storage stability of exhaled breath VOCs on thermal desorption adsorbent material is critical. To address this gap, exhaled breath was loaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 53 publications
3
70
1
Order By: Relevance
“…Concerns such as the stability of VOCs trapped onto sorbent materials, storage and also logistics are apparent. It has been shown that these tubes can be stored for up to 2 weeks prior to analysis (Harshman et al 2016; van der Schee et al 2013) whilst another study suggests longer (Kang and Paul Thomas 2016). Samples collected using this method can be analysed in the laboratory present in hospitals provided that the required analytical platform is available which would require a significant investment.…”
Section: Pre-concentration Methodsmentioning
confidence: 99%
“…Concerns such as the stability of VOCs trapped onto sorbent materials, storage and also logistics are apparent. It has been shown that these tubes can be stored for up to 2 weeks prior to analysis (Harshman et al 2016; van der Schee et al 2013) whilst another study suggests longer (Kang and Paul Thomas 2016). Samples collected using this method can be analysed in the laboratory present in hospitals provided that the required analytical platform is available which would require a significant investment.…”
Section: Pre-concentration Methodsmentioning
confidence: 99%
“…For instance, Koziel et al (2005) found that recovery of volatile organic compounds stored in sorbent tubes was reduced by 88.3% after only 120 hr at room temperature. Others have reported acceptable preservation for up to two weeks, but only when stored at 5–10°C (Harshman et al, 2016; Kang & Thomas, 2016; Van der Schee et al, 2012). Likewise, a number of studies have revealed retention biases for different compound classes following storage (Harshman et al, 2016; Kallenbach et al, 2014; Kücklich et al, 2017; Nair et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported acceptable preservation for up to two weeks, but only when stored at 5–10°C (Harshman et al, 2016; Kang & Thomas, 2016; Van der Schee et al, 2012). Likewise, a number of studies have revealed retention biases for different compound classes following storage (Harshman et al, 2016; Kallenbach et al, 2014; Kücklich et al, 2017; Nair et al, 2018). Hence, while these tubes may suffice for short‐term storage at ambient temperature, they are not a viable option for a large portion of field studies, particularly those that involve significant travel or lack the infrastructure to refrigerate or freeze samples.…”
Section: Introductionmentioning
confidence: 99%
“…124,125 Although breath samples can be analyzed by many analytical instruments, preservation of the sample integrity during sample storage and sampling process is critical for reliable analysis of VOCs in breath samples. [126][127][128][129][130][131] Tedlar bag is the most commonly accepted materials for collecting breath samples. 128,130,131 The storage of selected VOCs within sampling bags has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…[126][127][128][129][130][131] Tedlar bag is the most commonly accepted materials for collecting breath samples. 128,130,131 The storage of selected VOCs within sampling bags has been extensively studied. [126][127][128][129][130][131] However, most of the previous work studied VOC stability by spiking selected VOCs into air and nitrogen matrices.…”
Section: Introductionmentioning
confidence: 99%